(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
The neuroscience as study becomes multifaceted according to his epistemological construction, because from her there stem philosophical, ethical, moral, social, medical, neurological conceptions, which occur into a scientific framework of diverse ways of thinking. Inside this field, there is located the study of the epilepsy, like illness that it must be treated from these several dimensions, of holistic form; from his physiological, neurological, psychiatric frame, up to his aftereffect in the individual and his environment of life, to try to diminish the social impact of his suffering, both for the patient and for his existential context. The object of the present work is to know on the epilepsy, the quality of life about those who endure it, and to realize an approach of social nature. The used method is the bibliographical and documentary review. According to results of investigation, in Venezuela the medical treatment could be obviating important aspects as the adaptation of the individual to the social context and the acceptance of the same one without fears or rejection. He ends, that to propitiate quality of life for the epileptic patients is a need and social debt that it must be settled in the short term.